FT-IR spectroscopy: Principle, technique and mathematics - S. D. SAWANT; A. A. BARAVKAR; R. N. KALE (International Journal of Pharma and Bio Sciences, 2011)
Fourier Transform Infra Red spectroscopy (FT-IR) has wide applicability in structure elucidation, which are either synthesized chemically or of natural origin. Now a day, Fourier Transform Infra Red (FT-IR) Spectroscopy is extensively used for quantitative as well as for qualitative analysis in almost all fields of science. It has many advantages and applications as compared to dispersive infra red technology.